Migratures. A Scenic Self-Potrait: Woman-Migration-Mental Health - Rodríguez Barquero, Vivian (2024)
In this anthology, we propose a program of four micro-theater plays (each 15 minutes long): two plays inspired by and researched on autobiographical material of their authors and two other plays inspired by two stories selected from at least 30 biographies of migrant women residents of the South Caribbean of Costa Rica. They are powerful and interesting stories to write with scenic genres that could enhance the proposal of their authors.